2022
DOI: 10.1109/led.2022.3148669
|View full text |Cite
|
Sign up to set email alerts
|

Logic Compatible High-Performance Ferroelectric Transistor Memory

Abstract: Silicon ferroelectric field-effect transistors (FeFETs) with low-k interfacial layer (IL) between ferroelectric gate stack and silicon channel suffers from high write voltage, limited write endurance and large read-after-write latency due to early IL breakdown and charge trapping and detrapping at the interface. We demonstrate low voltage, high speed memory operation with high write endurance using an IL-free back-end-of-line (BEOL) compatible FeFET. We fabricate IL-free FeFETs with 28nm channel length and 126… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…All four terminals (gate, drain, source, and bulk) were held at 0V during this time. Although recent studies have shown much lower latency between WRITE and READ operations [31,32], this value has been optimized for the array-level operations with 28nm HKMG FeFETs (n-type) in 300mm wafers [33]. The pulse applied at the gate terminal during the WRITE operations aligns the ferroelectric dipoles according to their polarity, affecting the surface charge density of the channel, conductance of the channel (Gch), and the threshold voltage (Vth).…”
Section: Methodsmentioning
confidence: 99%
“…All four terminals (gate, drain, source, and bulk) were held at 0V during this time. Although recent studies have shown much lower latency between WRITE and READ operations [31,32], this value has been optimized for the array-level operations with 28nm HKMG FeFETs (n-type) in 300mm wafers [33]. The pulse applied at the gate terminal during the WRITE operations aligns the ferroelectric dipoles according to their polarity, affecting the surface charge density of the channel, conductance of the channel (Gch), and the threshold voltage (Vth).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of holes in the channel degrades the endurance most significantly as we have shown recently. 29 On the other hand, back end of the line (BEOL) FEFETs with non-Si channel such as with In 2 O 3 channel, operating in depletion 14 or fully depleted FEFETs, 30 have much higher endurance. In other words, complete assessment of endurance properties needs to be performed in FEFET structures with scavenged oxides (not in FE MOS capacitors).…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…Reducing the thickness of the IL or eliminating it altogether has been suggested as one of the key strategies to reduce the write voltage in FEFETs. 5,14,15 Techniques to reduce the IL thickness, often referred to as oxygen scavenging, were investigated in the context of the high-k-metal-gate technology development for standard complementary metal−oxide−semiconductor (CMOS) transistors, to reduce the effective oxide thickness (EOT) and improve the on-current. 16−18 Previous studies on amorphous dielectric (DE) HfO 2 gate oxides have successfully demonstrated significant EOT reduction by employing remote scavenging (sometimes called gettering) metal electrodes for SiO 2 IL scavenging.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations